2018
DOI: 10.1364/ao.57.002258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anisotropy on bit error rate for an asymmetrical Gaussian beam in a turbulent ocean

Abstract: Effect of anisotropy on the average bit error rate (BER) is investigated when an asymmetrical Gaussian beam is propagated in an anisotropic turbulent ocean. BER is found to decrease in response to an increase in anisotropy levels in the x and y directions. Higher average signal-to-noise ratio, wavelength, and microscale length yield smaller BER values. BER starts to rise with an increase in the asymmetrical beam source size in the x and y directions, source size ratio in the x and y directions, salinity and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although some portion of Hill's Model 1 is verified by the experimental data, the spectrum of Nikishov and Nikishov [28] has not yet been verified underwater [29]. In general, however, anisotropy in turbulence occurs quite frequently and reduces the scintillation and consequently affects the OWC system performance underwater in a positive manner [30][31][32]. Therefore, it is worth analysing the effects of anisotropy on OWC systems operating in strong oceanic turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Although some portion of Hill's Model 1 is verified by the experimental data, the spectrum of Nikishov and Nikishov [28] has not yet been verified underwater [29]. In general, however, anisotropy in turbulence occurs quite frequently and reduces the scintillation and consequently affects the OWC system performance underwater in a positive manner [30][31][32]. Therefore, it is worth analysing the effects of anisotropy on OWC systems operating in strong oceanic turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of anisotropic oceanic turbulence on the intensity fluctuations was discussed by Baykal [15,16]. Thereafter, the effect of anisotropic turbulence on the average bit error rate (BER) was further investigated when an asymmetrical Gaussian beam propagates in anisotropic turbulence [17]. The BER decreased in response to increased anisotropy levels in various directions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the atmospheric turbulence [19,[29][30][31] as well as the underwater [32,33] are anisotropic. Recently, many papers have been published about the effects of anisotropic underwater turbulence on the optical communication systems [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%